Enoxaparin Effect on Pregnancy Outcomes in a Patient with Elevated Plasminogen Activator Inhibitor-1 - Kathleen Minor; Heidi Leftwich (Case Reports in Obstetrics and Gynecology)
Background. Plasminogen activator inhibitor-1 (PAI-1) inhibits tPA and creates a prothrombotic state. Gene polymorphisms of PAI-1 are associated with elevated levels and adverse pregnancy outcomes. Case. A 36-year-old gravida 6, para 1-1-3-1 with elevated prepregnancy PAI-1 levels, a history of early-onset preeclampsia with severe features superimposed on chronic hypertension, intrauterine growth restriction (IUGR), and recurrent pregnancy loss (RPL), presented with a dichorionic-diamniotic twin gestation. She was managed with aspirin and enoxaparin and delivered appropriately grown twins at 36 weeks and 3 days, due to the development of preeclampsia superimposed on chronic hypertension. She was discharged not on enoxaparin and represented with pulmonary edema on postoperative day 8. Conclusion. It is reasonable to consider testing certain patients with recurrent pregnancy loss and/or early preeclampsia with severe features for PAI-1. If levels are elevated, treatment with prophylactic enoxaparin may be beneficial. Further research is needed to determine the effect of this therapy in patients with exceedingly poor perinatal outcomes to better assess for any impact on improved outcomes.